Intergenerational mobility in occupational choices: Are there gender differences in Ghana? - Priscilla Twumasi Baffour; Festus Ebo Turkson; Ibrahim Mohammed; Wassiuw Abdul Rahaman (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
Historically, the issue of intergenerational evolution of income, wealth, and socioeconomic status has been the subject of considerable research in the analysis of inequality. Such intergenerational linkages are anticipated to come from two sources: first, the inheritance of innate abilities and social network of family from parents by children; and second, capital market imperfections which present barriers to human capital investment. Consequently, using the correlation matrix and multivariate probit model, this study investigates the extent to which the occupational choices of mothers and fathers are intergenerationally transmitted to their offspring using the latest round of the Ghana Living Standards Survey. Findings indicate that intergenerational linkages are important in Ghana; specifically, the results show a positive significant influence of parents' occupation on children's occupation. Mother's occupation is found to have a much greater impact on offspring's occupation than that of fathers. In terms of gender differences, there is the evidence of a dependency burden in the occupational choice of daughters, as having children under five is found to be negatively associated with the participation of women in formal occupations such as services and sales. The findings highlight the fact that children of parents employed in high-paying and prestigious occupations in Ghana are more likely to be employed in similar occupations themselves. In order to bridge the gap in social mobility, policy-makers need to channel attention towards the elimination of capital market imperfections to encourage investment in human capital among the poor in society and to facilitate social mobility through the provision of economic opportunities.
Keywords: C35; J16; J24; J62; 330; intergenerational transmission; socioeconomic status; multivariate probit; occupation; human capital; gender